2014
DOI: 10.3389/fnut.2014.00007
|View full text |Cite
|
Sign up to set email alerts
|

Neural Responses to Visual Food Cues According to Weight Status: A Systematic Review of Functional Magnetic Resonance Imaging Studies

Abstract: Emerging evidence from recent neuroimaging studies suggests that specific food-related behaviors contribute to the development of obesity. The aim of this review was to report the neural responses to visual food cues, as assessed by functional magnetic resonance imaging (fMRI), in humans of differing weight status. Published studies to 2014 were retrieved and included if they used visual food cues, studied humans >18 years old, reported weight status, and included fMRI outcomes. Sixty studies were identified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
180
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(207 citation statements)
references
References 130 publications
(356 reference statements)
16
180
1
Order By: Relevance
“…It could be argued that the effects of the weight loss may have confounded the decreasing effects of liraglutide on CNS activation after 12 weeks. However, if anything, fMRI studies investigating the effect of weight loss on CNS responses to food pictures show that weight reduction may be associated with decreased CNS activation in areas involved in food motivation and reward (19,20). As a result, an effect of weight loss on the CNS would have strengthened the decreasing effect of liraglutide on CNS activation, and weight loss therefore cannot explain the absence of an effect of liraglutide on the CNS after 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…It could be argued that the effects of the weight loss may have confounded the decreasing effects of liraglutide on CNS activation after 12 weeks. However, if anything, fMRI studies investigating the effect of weight loss on CNS responses to food pictures show that weight reduction may be associated with decreased CNS activation in areas involved in food motivation and reward (19,20). As a result, an effect of weight loss on the CNS would have strengthened the decreasing effect of liraglutide on CNS activation, and weight loss therefore cannot explain the absence of an effect of liraglutide on the CNS after 12 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the response in the hypothalamus/ventral striatum was modulated by the expected energy content of the food. 15 More recently, Pursey et al (2014) conducted a meta-analysis of 60 different neuroimaging studies (involving a total of 1565 participants) that had assessed the neural response to visual food cues as a function of the weight of their participants. In this case, the results revealed that obese individuals exhibited a greater increase in neural activation in response to food as compared to non-food images, especially for high-calorie foods, in those brain regions that are associated with reward processing (e.g., the insula and OFC), reinforcement and adaptive learning (the amygdala, putamen, and OFC), emotional processing (the insula, amygdala, and cingulate gyrus), recollective and working memory (the amygdala, hippocampus, thalamus, posterior cingulate cortex, and caudate), executive functioning (the prefrontal cortex (PFC), caudate, and cingulate gyrus), decision making (the OFC, PFC, and thalamus), visual processing (the thalamus and fusiform gyrus), and motor learning and coordination, such as hand-to-mouth movements and swallowing (the insula, putamen, thalamus, and caudate).…”
Section: Neural Substrates Underlying the Processing Of Visual Food Cuesmentioning
confidence: 99%
“…While the reviewed studies show a blunted striatal response in patients with schizophrenia (or depression) and their relatives, the picture is less clear in obesity. As explained above, while we propose to explain obesity in schizophrenia as resulting from a decreased striatal signal during reward anticipation, some obesity studies point to enhanced cue reactivity (Pursey et al, 2014), possibly reflecting a distinct pathway to obesity. However, the striking differences in the various paradigms, populations, and methods used to study obesity make it hard to generalize across studies.…”
Section: Obesity-related Changes In Striatal Reward Processingmentioning
confidence: 84%
“…Most studies of cue processing presented images of appetizing food stimuli to obese patients. These studies found an increase in striatal reactivity when participants viewed these stimuli (Pursey et al, 2014). It is hard to relate these studies to studies using MID tasks due to several methodological issues: monetary (MID) vs. food rewards, eventrelated (MID) vs. block designs, uncontrolled satiation status (MID) vs. fasting or satiated participants, operant (MID) vs. Pavlovian conditioning, images often not controlled for calorie content etc.…”
Section: Obesity-related Changes In Striatal Reward Processingmentioning
confidence: 99%